Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1186/s40478-023-01578-x
|View full text |Cite
|
Sign up to set email alerts
|

Senescence-related impairment of autophagy induces toxic intraneuronal amyloid-β accumulation in a mouse model of amyloid pathology

Abstract: Aging is the main risk factor for Alzheimer’s disease (AD) and other neurodegenerative pathologies, but the molecular and cellular changes underlying pathological aging of the nervous system are poorly understood. AD pathology seems to correlate with the appearance of cells that become senescent due to the progressive accumulation of cellular insults causing DNA damage. Senescence has also been shown to reduce the autophagic flux, a mechanism involved in clearing damaged proteins from the cell, and such impair… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 122 publications
(173 reference statements)
1
8
0
Order By: Relevance
“…Our transcriptomic analysis suggests one such pathological mechanism may be impairment of autophagy-lysosomal activity in vulnerable neurons which may lead to intraAβ accumulation, as previously observed in AD mouse models 19,20 . Changes in the autophagy lysosomal pathway specific to AT8 + neurons have been observed before in patients affected by AD 47 and tauopathies 66 , showing however an increase in p62/SQSTM1 and LC3 expression, respectively.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Our transcriptomic analysis suggests one such pathological mechanism may be impairment of autophagy-lysosomal activity in vulnerable neurons which may lead to intraAβ accumulation, as previously observed in AD mouse models 19,20 . Changes in the autophagy lysosomal pathway specific to AT8 + neurons have been observed before in patients affected by AD 47 and tauopathies 66 , showing however an increase in p62/SQSTM1 and LC3 expression, respectively.…”
Section: Discussionsupporting
confidence: 73%
“…To explore the relative expression of genes of the autophagy-lysosomal pathway previously associated with AD pathology including intraAβ accumulation in amyloid mouse models 19,20 , we tested for differential expression of genes involved in autophagy 55 and neurodegenerative diseases (AD and FTD; Table 6) 56 . We found that majority of genes tested were downregulated relatively specifically in the Exc−L5−RORB−LINC01202 cluster (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies employing a mouse model of AD (APP/PS1) suggested a link between oxidative stress and cellular senescence, wherein, mice exposed to prolonged oxidative stress exhibited cellular alterations that closely resembled those observed in various senescent states like elevated expression of SA-β-gal, cell cycle arrest, and changes in the shape and structure of cells [ 45 , 46 ]. Zhang et al demonstrated the upregulation of ROS production and p53 expression in a human astrocyte cell line (U87) upon exposure to Aβ1-40, and this effect was reversed by galantamine pretreatment [ 47 ].…”
Section: Redox Dyshomeostasis and Cellular Senescence In Admentioning
confidence: 99%